Keseimbangan asam-basa tubuh dan kejadian sindrom metabolik pada remaja obesitas - Firdananda Fikri Jauharany; Nurmasari Widyastuti (Jurnal Gizi Klinik Indonesia, 2017)
Background: The prevalence of metabolic syndrome increased in young population, indicated by the rise in obesity among children and adolescent. The Western dietary pattern was one of the causes. A Western diet rich in animal protein can produce acid during the metabolic process and may cause an acid-excess in the body (dietary acid load). This process was contributed to acid-base balance through the metabolism of sulfur-containing amino acids (cysteine and methionine) which produce H+ ions as well as lowering the pH.Objective: To examine the association between acid-base balance and components of metabolic syndrome among obese adolescent.Method: A cross-sectional study was conducted on 40 obese adolescents in Semarang high school. We measured Potential Renal Acid Load (PRAL) score and pH urine as an acid-base indicator. MetS are defined ≥ 3 following risk factors: waist circumference ≥90th percentile, blood pressure ≥90th percentile, triglycerides ≥110 mg/dl, HDL levels ≤40 mg/dl, and fasting blood glucose levels ≥110 mg/dl. Normality test used the Shapiro-Wilk test (n <50). The bivariate analysis used Pearson test, Rank-Spearman test, and Chi-Square test. The multivariate analysis used Multivariate Linear Regression analysis of Backward.Results: PRAL score was associated with waist circumference (r=0,347; p=0,028), sistolic blood pressure (r=0,590; p=<0,001), diastolic blood pressure (r=0,668; p=<0,001), and triglyceride levels (r=0,362; p=0,022). pH urin was not associated with any risk factors of MetS.Conclusion: High dietary acid load may be a risk factor for the development of MetS.